2018
DOI: 10.1002/berj.3472
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence (EI) and self‐directed learning: Examining their relation and contribution to better student learning outcomes in higher education

Abstract: Self-directed learning is recognised as a key goal of higher education. To facilitate self-directed learning, emotional intelligence (EI), which encompasses the ability to regulate one's own emotions and to generate positive emotions, is important. The present study aimed to examine the effects of EI on self-directed learning and how EI and self-directed learning contribute to key learning outcomes in higher education, including grade point average (GPA), generic learning outcomes (including social, cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(152 citation statements)
references
References 78 publications
9
130
1
1
Order By: Relevance
“…Much research has proven the impact of modern learning techniques, such as the projectbased experiential learning, the problem-based learning, and game-based learning, which basically follow a flipped education strategy where students become self-directed learners and educators play the role of coach or facilitator, such as Mercer et al (2017), Moore, Jones and Frazier (2017), Murillo-Zamoranoa, Sáncheza and Godoy-Caballero (2019), Rospigliosi (2019), Tomas et al (2019), and Zhoc et al (2018). However, no one single programme has been designed in a way that serves the changed learning needs of generation Z, particularly for developing sustainable leadership skills, which would be of immediate use in today's work world.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research has proven the impact of modern learning techniques, such as the projectbased experiential learning, the problem-based learning, and game-based learning, which basically follow a flipped education strategy where students become self-directed learners and educators play the role of coach or facilitator, such as Mercer et al (2017), Moore, Jones and Frazier (2017), Murillo-Zamoranoa, Sáncheza and Godoy-Caballero (2019), Rospigliosi (2019), Tomas et al (2019), and Zhoc et al (2018). However, no one single programme has been designed in a way that serves the changed learning needs of generation Z, particularly for developing sustainable leadership skills, which would be of immediate use in today's work world.…”
Section: Resultsmentioning
confidence: 99%
“…A consequence of SIB and another core learning outcome believed to pave the way for developing workplace competencies, self-directed learning is recognised as the ability to willingly initiate, prepare, execute, and evaluate one's own learning without the need to be guided by other people (Kos et al, 2017;Morris, 2018;Zhoc et al, 2018). Although a critical leadership characteristic, both academic and vocational educational institutions have not fully incorporated SDL into their programmes (Morris, 2018).…”
Section: Self-directed Learning (Sdl)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to note that prior empirical studies have highlighted positive association of self-directed learning with academic performance (Lounsbury et al, 2009;Zhoc and Chen, 2016;Zhoc et al, 2018), as well as lifelong learning (Salleh et al, 2019), in higher education. In their meta-analysis, Boyer et al (2014) found that self-directed learning has a positive relationship with a range of personality factors such as intrinsic motivation, internal locus of control, academic achievement and help seeking behavior.…”
Section: Self-directed Learningmentioning
confidence: 99%
“…As mentioned previously, students with higher EI are not only capable of dealing with their own emotions and others', they also manage to control any feelings of frustration to remain focused on important work issues. In this sense, Zhoc, Chung, and King (2018) provide empirical evidence that students who are more emotionally intelligent are more self-directed. Their results suggest that the three emotional abilities-emotional regulation of the self (ERS), appraisal of emotions in the self (AES), and emotional regulation of others (ERO)were positively related to SDL.…”
Section: Ei In Self-directed Online Learning Environmentsmentioning
confidence: 97%